2012
DOI: 10.1074/jbc.m112.346767
|View full text |Cite
|
Sign up to set email alerts
|

DEF6, a Novel Substrate for the Tec Kinase ITK, Contains a Glutamine-rich Aggregation-prone Region and Forms Cytoplasmic Granules that Co-localize with P-bodies

Abstract: Background: DEF6 is recruited to the immunological synapse upon T cell receptor-mediated signaling regulating inflammatory responses including Experimental Autoimmune Encephalomyelitis. Results: DEF6 is a substrate for ITK and forms granules co-localizing with P-bodies. Conclusion: DEF6 granule formation is likely to be mediated by unmasking a Q-rich coiled-coil region in the C terminus. Significance: Discovery of a potential link between T cell receptor-mediated signaling and translation regulation in P-bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…This stretch has a pI of 4.8 and is rich in glutamine and glutamic acid, which together account for 41% of the 81 aa. Glutamine-rich regions were described as modules involved in multimerization of proteins even if present in coiled-coil regions (58), and the only protein closely related to SWAP-70, DEF6, also harbors a Gln/Glu-rich (31%) stretch suggested to be involved in its multimerization, which, however, is functionally different and not related to F-actin dynamics (59).…”
Section: Discussionmentioning
confidence: 99%
“…This stretch has a pI of 4.8 and is rich in glutamine and glutamic acid, which together account for 41% of the 81 aa. Glutamine-rich regions were described as modules involved in multimerization of proteins even if present in coiled-coil regions (58), and the only protein closely related to SWAP-70, DEF6, also harbors a Gln/Glu-rich (31%) stretch suggested to be involved in its multimerization, which, however, is functionally different and not related to F-actin dynamics (59).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SWAP-70 and DEF6 can be found in cytoplasmic and nuclear compartments and can also be recruited to the plasma membrane in a stimulation-dependent manner [1417]. Recent studies have furthermore shown that Def6 contains a glutamine-rich coiled-coil region within its C-terminal region that enables it to aggregate and localize to P-bodies upon cellular stress [18]. …”
Section: The Swef Proteins: General Characteristicsmentioning
confidence: 99%
“…Indeed the absence of DEF6 results in a number of abnormalities in T H cells that include aberrancies in the ability of the TCR to properly gauge the strength of engagement, likely due to improper cytoskeletal reorganization and immunological synapse formation, and defective T H 1 and T H 2 responses that have been deemed secondary to impaired NFAT activation [22, 23]. Additional regulatory events, such as Itk-mediated phosphorylation, have also been recently shown to contribute to the regulation of DEF6 localization and activity [18, 24]. …”
Section: Role Of the Swef Proteins In T Cellsmentioning
confidence: 99%
“…12 A number of specific tyrosines targeted by Itk have been identified, including Y783 of PLCγ1, Y180 of Itk, Y173 of SLP-76 and, recently, Y210 as well as Y222 of DEF6. 1317 Among these Itk-mediated phosphorylation on Y783 of PLCγ1 is the best studied and most important in the context of T cell signaling. Phosphorylation on PLCγ1 Y783 activates the lipase activity of PLCγ1, which generates two essential secondary messengers, diacylglycerol and inositol trisphosphate, by hydrolyzing phosphatidylinositol 4,5-bisphosphate.…”
Section: Introductionmentioning
confidence: 99%